Preparation method of composite coating decorative embossed glass with high hardness and high adhesion

By fine pattern design and laser engraving of the PET diaphragm, combined with UV ink and aqueous acrylic varnish, the problem of single existing glass coating process is solved, and a composite coating with high hardness and high adhesion is achieved The preparation of decorative embossed glass improves production efficiency and product performance.

CN118954969BActive Publication Date: 2025-02-25LONGKOU KENUOER GLASS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411419959.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing glass coating production process is single, and it is difficult to achieve composite coating decorative embossed glass with high hardness and high adhesion.

Method used

PET diaphragm is used for fine pattern design and laser direct writing scanning engraving, combined with UV ink for imprinting, and back-sealing treatment is used for aqueous acrylic varnish to obtain a composite coating with high hardness and high adhesion through rapid curing of UV.

Benefits of technology

Saving manufacturing time, reducing production costs, improving production efficiency, and obtaining composite coatings with high hardness, high adhesion and aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954969B_ABST
    Figure CN118954969B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of tempered glass technology, and specifically to a method for preparing a composite coating decorative embossed glass with high hardness and high adhesion, comprising the following steps: Step 1: finely designing a pattern on a PET film, and then laser direct writing scanning and engraving the PET film according to the designed pattern; Step 2: according to the texture obtained in Step 1, using UV ink to perform embossing treatment on the tin surface of the tempered glass, and then performing a curing treatment to obtain the tempered glass after embossing; Step 3: using water-based acrylic varnish to perform a back cover on the air surface of the tempered glass obtained in Step 2, and after curing treatment, a finished product is obtained. The present invention uses water-based acrylic varnish to print on the air surface of the glass as a back cover, and after curing treatment, it is used as a protective layer on the air exposed surface of the glass, which can protect the glass and prevent the glass from being scratched, and has the advantages of high strength, high hardness, high adhesion and good aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of tempered glass technology, and in particular to a method for preparing composite coating decorative embossed glass with high hardness and high adhesion. Background Art

[0002] With the advancement of information technology and the development of design aesthetics, smart terminal products such as mobile phones, laptops, and tablets have been deeply integrated and widely penetrated into all aspects of human society. In the new era, product updates and iterations are getting faster and faster. In the situation where performance is gradually becoming excessive, major manufacturers are increasingly inclined to improve the appearance design of products as the key to attracting consumers. Among them, the application of optical texture is to construct micro-nano-level textures to refract, diffuse, diffract or interfere light waves, thereby achieving a variety of rich and cool light and shadow effects.

[0003] However, with the increase in product models, the demand for tempered glass is also increasing, and the appearance of glass is also solidified. Today, the glass industry is constantly developing, and the glass coating production process is basically finalized on screen printing, with few subsequent changes and a single process form. Therefore, this scheme provides a method for preparing composite coating decorative embossed glass. The present invention is a new production process that is more convenient and simple to operate, and the composite coating has the advantages of high hardness and high adhesion. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing a composite coating decorative embossed glass with high hardness and high adhesion.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] A method for preparing composite coating decorative embossed glass with high hardness and high adhesion, comprising the following steps:

[0007] Step 1: Design a detailed pattern on the PET film, and then perform laser direct writing scanning and engraving on the PET film according to the designed pattern;

[0008] Step 2: According to the texture obtained in step 1, the tin surface of the tempered glass is embossed with UV ink, and then cured to obtain the embossed tempered glass;

[0009] Step 3: The air surface of the tempered glass obtained in step 2 is sealed with water-based acrylic varnish, and after curing, a finished product is obtained.

[0010] Preferably, in step 2, the ink is subjected to UV curing after embossing, with a UV wavelength of 365 nm and a radiation dose of 100-200 mW / cm 2 , the curing time is 1-5min.

[0011] Preferably, in step 3, the curing is carried out by UV curing, the UV wavelength is 365nm, and the radiation amount is 100-200mW / cm 2 , the curing time is 1-5min.

[0012] Preferably, in step 3, the water-based acrylic varnish, calculated in parts by weight, comprises:

[0013] 70-90 parts of water-based oligomeric acrylic emulsion, 8-16 parts of acrylic acid, 1-2 parts of dispersant, 0.5-1 parts of defoamer, 0.04-0.1 parts of photosensitizer, 0.6-1.2 parts of leveling agent, 0.1-0.3 parts of neutralizer and 25-35 parts of deionized water.

[0014] Preferably, the preparation method of the aqueous oligomeric acrylic emulsion comprises:

[0015] S1. Preparation of olefin benzimidazole:

[0016] Weigh 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol, mix them, stir them until they are uniform, add a catalyst, heat them to reflux, keep them warm and stir for 4-6 hours, and after the reaction is completed, remove impurities by rotary evaporation to obtain olefin benzimidazole;

[0017] S2, preparing pre-reaction solution:

[0018] The olefin benzimidazole, the first emulsifier and deionized water are mixed, and then the acrylic acid monomer is added, and the mixture is stirred and mixed for 20-40 minutes to obtain a pre-reaction solution;

[0019] S3, preparing modified oligomeric emulsion:

[0020] Under the protection of nitrogen, the initiator, the second emulsifier and deionized water are mixed and heated to 65-75°C. After stirring evenly, the pre-reaction liquid is added dropwise, and the dropping time is controlled to be 1-2h. After the dropping is completed, the temperature is raised to 75-85°C, stirred for 1-2h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0021] Preferably, in S1, the mass ratio of 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol is 1.4-1.8:0.8-1.2:10-20.

[0022] Preferably, in S1, the catalyst is triethylamine, and the added amount is 3%-5% of the mass of 3-methyl-2-butenal.

[0023] Preferably, in S2, the mass ratio of olefin benzimidazole, acrylic monomer, first emulsifier and deionized water is 0.3-0.7:1.7-3.9:0.03-0.08:20-30.

[0024] Preferably, in S2, the acrylic acid monomer includes acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, and cyclohexyl methacrylate, and the mass ratio of acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, and cyclohexyl methacrylate is 0.3-0.5:0.2-0.6:0.3-0.7:0.1-0.5:0.4-0.8:0.4-0.8.

[0025] Preferably, in S3, the initiator is one of sodium persulfate, potassium persulfate and ammonium persulfate.

[0026] Preferably, in S3, the mass ratio of the initiator, the second emulsifier, the pre-reaction liquid and the deionized water is 0.05-0.1:4-8:50-100:50-100.

[0027] Preferably, the first emulsifier in S2 and the second emulsifier in S3 are the same, and are one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate.

[0028] Preferably, the dispersant is Digo 760W, the defoamer is Digo 902W, the photosensitizer is photosensitizer 1173, the leveling agent is BYK-333, and the neutralizer is ethanolamine.

[0029] Preferably, the preparation method of the water-based acrylic varnish comprises:

[0030] Acrylic acid, dispersant and deionized water are mixed, stirred for 5-10 minutes, and then water-based oligomeric acrylic emulsion is added. After stirring for 20-30 minutes, photosensitizer, defoamer, leveling agent and neutralizer are added. The mixture is stirred for 5-10 minutes in a dark environment to obtain water-based acrylic varnish.

[0031] The beneficial effects of the present invention are:

[0032] 1. The scheme of the present invention uses UV rapid curing, which saves manufacturing time, saves a lot of space, greatly reduces production costs, and improves production efficiency. The present invention uses water-based acrylic varnish to print on the air side of the glass as a back cover. After curing, it is used as a protective layer on the air-exposed surface of the glass, which can protect the glass and prevent it from being scratched. It has the advantages of high strength, high hardness, high adhesion and good aging resistance.

[0033] 2. The water-based acrylic varnish prepared by the present invention can be cured quickly after UV light treatment, and compared with conventional acrylic inks, it is not only stronger, but also has greater hardness and better adhesion. The main raw material of the water-based acrylic varnish, the water-based oligomeric acrylic emulsion, is synthesized by oligomerization of olefin benzimidazole and acrylic acid monomer, and then various additives are added and mixed uniformly to obtain the water-based acrylic varnish.

[0034] 3. In the preparation of water-based oligomeric acrylic emulsion, olefin-benzimidazole is obtained by reacting 3-methyl-2-butenal containing olefin and aldehyde groups with 2-aminobenzimidazole containing amino groups under alkaline catalysis. The prepared olefin-benzimidazole is a benzimidazole compound containing olefin and Schiff base groups, which participates in the incomplete oligomerization reaction of acrylic acid as a modifier to form an oligomeric acrylic emulsion. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0036] Figure 1 is a schematic diagram of the appearance of the tempered glass after printing prepared in Example 1 of the present invention;

[0037] Figure 2 It is a schematic diagram of the appearance of the finished composite coating decorative embossed glass product prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0039] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0040] The present invention will be further described below in conjunction with the following examples.

[0041] Example 1

[0042] A method for preparing composite coating decorative embossed glass with high hardness and high adhesion, comprising the following steps:

[0043] Step 1: Design a detailed pattern on the PET film, and then perform laser direct writing scanning and engraving on the PET film according to the designed pattern;

[0044] Step 2: According to the texture obtained in step 1, use UV ink to emboss the tin surface of the tempered glass, and then undergo curing to obtain the tempered glass after embossing, such as Figure 1 As shown;

[0045] Step 3: Use water-based acrylic varnish to seal the air surface of the tempered glass after the stamping obtained in step 2, and after curing, obtain the finished product, such as Figure 2 shown.

[0046] In step 2, the ink is embossed and then UV cured, with a UV wavelength of 365nm and a radiation dose of 150mW / cm 2 , the curing time is 3min.

[0047] In step 3, the curing is carried out using UV curing, with a UV wavelength of 365nm and a radiation dose of 150mW / cm 2 , the curing time is 3min.

[0048] In step 3, the water-based acrylic varnish is calculated by weight and includes:

[0049] 80 parts of water-based oligomeric acrylic emulsion, 12 parts of acrylic acid, 1.5 parts of dispersant Digo 760W, 0.6 parts of defoamer Digo 902W, 0.07 parts of photosensitizer 1173, 0.9 parts of leveling agent BYK-333, 0.2 parts of neutralizer (ethanolamine) and 30 parts of deionized water.

[0050] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0051] S1. Preparation of olefin benzimidazole:

[0052] Weigh 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol, mix them in a mass ratio of 1.6:1:15, stir them until they are uniform, add triethylamine as a catalyst in an amount of 4% of the mass of 3-methyl-2-butenal, heat to reflux, keep stirring for 5 hours, and after the reaction is completed, remove the solvent and impurities by rotary evaporation to obtain olefin benzimidazole;

[0053] S2, preparing pre-reaction solution:

[0054] Mix olefin benzimidazole, sodium dodecyl sulfate and deionized water, and then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate and cyclohexyl methacrylate, the mass ratio of olefin benzimidazole, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium dodecyl sulfate and deionized water is 0.5:0.4:0.4:0.5:0.3:0.6:0.6:0.05:25, and stir and mix thoroughly for 30 minutes to obtain a pre-reaction solution;

[0055] S3, preparing modified oligomeric emulsion:

[0056] Under the protection of nitrogen, sodium persulfate, sodium dodecyl sulfate and deionized water were mixed and heated to 70°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of sodium persulfate, sodium dodecyl sulfate, pre-reaction liquid and deionized water was 0.07:6:50:80. The dropping time was controlled to be 1.5h. After the dropwise addition was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0057] The preparation method of water-based acrylic varnish comprises:

[0058] Acrylic acid, dispersant and deionized water were mixed, stirred for 5 minutes, and then water-based oligomeric acrylic emulsion was added. After stirring for 30 minutes, photosensitizer, defoamer, leveling agent and neutralizer were added, and stirred for 10 minutes in the dark to obtain water-based acrylic varnish.

[0059] Example 2

[0060] A method for preparing a composite coating decorative embossed glass with high hardness and high adhesion, which is different from Example 1 in that the composition and content of the water-based acrylic varnish are different.

[0061] In step 3, the water-based acrylic varnish is calculated by weight and includes:

[0062] 70 parts of water-based oligomeric acrylic emulsion, 8 parts of acrylic acid, 1 part of dispersant Digo 760W, 0.5 parts of defoamer Digo 902W, 0.04 parts of photosensitizer 1173, 0.6 parts of leveling agent BYK-333, 0.1 parts of neutralizer (ethanolamine) and 25 parts of deionized water.

[0063] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0064] S1. Preparation of olefin benzimidazole:

[0065] Weigh 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol, mix them in a mass ratio of 1.4:0.8:10, stir them until they are uniform, add triethylamine as a catalyst in an amount of 3% of the mass of 3-methyl-2-butenal, heat to reflux, keep warm and stir for 4 hours, and after the reaction is completed, rotary evaporation to remove impurities to obtain olefin benzimidazole;

[0066] S2, preparing pre-reaction solution:

[0067] Mix olefin benzimidazole, sodium dodecylbenzene sulfonate and deionized water, then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate and cyclohexyl methacrylate, the mass ratio of olefin benzimidazole, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium dodecylbenzene sulfonate and deionized water is 0.3:0.3:0.2:0.3:0.1:0.4:0.4:0.03:20, stir and mix thoroughly for 20 minutes to obtain a pre-reaction solution;

[0068] S3, preparing modified oligomeric emulsion:

[0069] Under the protection of nitrogen, potassium persulfate, sodium dodecylbenzene sulfonate and deionized water were mixed and heated to 65°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of potassium persulfate, sodium dodecylbenzene sulfonate, pre-reaction liquid and deionized water was 0.05:4:50:50. The dropping time was controlled to be 1 hour. After the dropwise addition was completed, the temperature was raised to 75°C, stirred for 1 hour, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0070] The preparation method of water-based acrylic varnish comprises:

[0071] Acrylic acid, dispersant and deionized water were mixed, stirred for 5 minutes, and then water-based oligomeric acrylic emulsion was added. After stirring for 20 minutes, photosensitizer, defoamer, leveling agent and neutralizer were added, and stirred for 5 minutes in the dark to obtain water-based acrylic varnish.

[0072] Example 3

[0073] A method for preparing a composite coating decorative embossed glass with high hardness and high adhesion, which is different from Example 1 in that the composition and content of the water-based acrylic varnish are different.

[0074] In step 3, the water-based acrylic varnish is calculated by weight and includes:

[0075] 90 parts of water-based oligomeric acrylic emulsion, 16 parts of acrylic acid, 2 parts of dispersant Digo 760W, 1 part of defoamer Digo 902W, 0.1 parts of photosensitizer 1173, 1.2 parts of leveling agent BYK-333, 0.3 parts of neutralizer (ethanolamine) and 35 parts of deionized water.

[0076] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0077] S1. Preparation of olefin benzimidazole:

[0078] Weigh 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol, mix them in a mass ratio of 1.8:1.2:20, stir them until they are uniform, add triethylamine as a catalyst in an amount of 5% of the mass of 3-methyl-2-butenal, heat to reflux, keep stirring for 6 hours, and after the reaction is completed, remove impurities by rotary evaporation to obtain olefin benzimidazole;

[0079] S2, preparing pre-reaction solution:

[0080] Mix olefin benzimidazole, sodium hexadecyl sulfate and deionized water, and then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate and cyclohexyl methacrylate, the mass ratio of olefin benzimidazole, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium hexadecyl sulfate and deionized water is 0.7:0.5:0.6:0.7:0.5:0.8:0.8:0.08:30, and stir and mix for 40 minutes to obtain a pre-reaction solution;

[0081] S3, preparing modified oligomeric emulsion:

[0082] Under the protection of nitrogen, ammonium persulfate, sodium hexadecyl sulfate and deionized water were mixed and heated to 75°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of ammonium persulfate, sodium hexadecyl sulfate, pre-reaction liquid and deionized water was 0.1:8:100:100. The dropping time was controlled to be 2h. After the dropwise addition was completed, the temperature was raised to 85°C, stirred for 2h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0083] The preparation method of water-based acrylic varnish comprises:

[0084] Acrylic acid, dispersant and deionized water were mixed, stirred for 10 minutes, and then water-based oligomeric acrylic emulsion was added. After stirring for 30 minutes, photosensitizer, defoamer, leveling agent and neutralizer were added, and stirred for 10 minutes in the dark to obtain water-based acrylic varnish.

[0085] Comparative Example 1

[0086] A method for preparing composite coating decorative embossed glass is different from Example 1 in that the aqueous oligomeric acrylic emulsion in the aqueous acrylic varnish component used in step 3 is prepared differently, and the remaining components and preparation process are the same.

[0087] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0088] S1. Preparation of pre-reaction solution:

[0089] Mix sodium dodecyl sulfate and deionized water, then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, and cyclohexyl methacrylate, the mass ratio of acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium dodecyl sulfate and deionized water is 0.9:0.4:0.5:0.3:0.6:0.6:0.05:25, and stir and mix thoroughly for 30 minutes to obtain a pre-reaction solution;

[0090] S2. Preparation of modified oligomeric emulsion:

[0091] Under the protection of nitrogen, sodium persulfate, sodium dodecyl sulfate and deionized water were mixed and heated to 70°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of sodium persulfate, sodium dodecyl sulfate, pre-reaction liquid and deionized water was 0.07:6:50:80. The dropping time was controlled to be 1.5h. After the dropwise addition was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0092] Comparative Example 2

[0093] A method for preparing composite coating decorative embossed glass is different from Example 1 in that the aqueous oligomeric acrylic emulsion in the aqueous acrylic varnish component used in step 3 is prepared differently, and the remaining components and preparation process are the same.

[0094] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0095] S1. Preparation of pre-reaction solution:

[0096] Mix 2-aminobenzimidazole, sodium dodecyl sulfate and deionized water, and then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate and cyclohexyl methacrylate; the mass ratio of 2-aminobenzimidazole, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium dodecyl sulfate and deionized water is 0.5:0.4:0.4:0.5:0.3:0.6:0.6:0.05:25; stir and mix thoroughly for 30 minutes to obtain a pre-reaction solution;

[0097] S2. Preparation of modified oligomeric emulsion:

[0098] Under the protection of nitrogen, sodium persulfate, sodium dodecyl sulfate and deionized water were mixed and heated to 70°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of sodium persulfate, sodium dodecyl sulfate, pre-reaction liquid and deionized water was 0.07:6:50:80. The dropping time was controlled to be 1.5h. After the dropwise addition was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0099] Comparative Example 3

[0100] A method for preparing composite coating decorative embossed glass is different from Example 1 in that the aqueous oligomeric acrylic emulsion in the aqueous acrylic varnish component used in step 3 is prepared differently, and the remaining components and preparation process are the same.

[0101] The preparation method of the water-based oligomeric acrylic emulsion comprises:

[0102] S1. Preparation of pre-reaction solution:

[0103] Mix 3-methyl-2-butenal, sodium dodecyl sulfate and deionized water, and then add acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate and cyclohexyl methacrylate; the mass ratio of 3-methyl-2-butenal, acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, cyclohexyl methacrylate, sodium dodecyl sulfate and deionized water is 0.5:0.4:0.4:0.5:0.3:0.6:0.6:0.05:25, and stir and mix thoroughly for 30 minutes to obtain a pre-reaction solution;

[0104] S2. Preparation of modified oligomeric emulsion:

[0105] Under the protection of nitrogen, sodium persulfate, sodium dodecyl sulfate and deionized water were mixed and heated to 70°C. After stirring evenly, the pre-reaction liquid was added dropwise. The mass ratio of sodium persulfate, sodium dodecyl sulfate, pre-reaction liquid and deionized water was 0.07:6:50:80. The dropping time was controlled to be 1.5h. After the dropwise addition was completed, the temperature was raised to 80°C, stirred for 1.5h, and cooled to room temperature to obtain an aqueous oligomeric acrylic emulsion.

[0106] The performance of the bottom layer (water-based acrylic varnish layer) on the air surface of the composite coating decorative embossed glass prepared in Example 1 and Comparative Examples 1-3 was tested and compared, including hardness, adhesion, impact resistance, and aging resistance. The hardness test reference standard GB / T 6739-2022, the adhesion test reference standard GB / T 9286-2021, and the impact resistance test reference standard GB / T 1732-2020. The aging resistance was tested by irradiating the surface gloss retention of the paint film with a QUV aging instrument UVB-3B lamp for 500 hours.

[0107] The results are shown in Table 1:

[0108] Table 1 Comparison of performance of different embossed glass sealing layers

[0109]

[0110] It can be seen from Table 1 that the sealing layer on the air side of the composite coating decorative embossed glass prepared in Example 1 of the present invention not only has better impact resistance, but also has the advantages of high hardness, strong adhesion and good aging resistance.

[0111] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0112] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a composite coating decorative embossed glass with high hardness and high adhesion, characterized in that: The following steps are involved: Step 1: Design a detailed pattern on the PET film, and then perform laser direct writing scanning and engraving on the PET film according to the designed pattern; Step 2: According to the texture obtained in step 1, the tin surface of the tempered glass is embossed with UV ink, and then subjected to curing treatment to obtain the embossed tempered glass; Step 3: The air surface of the tempered glass obtained in step 2 is sealed with water-based acrylic varnish, and after curing, a finished product is obtained; In step 3, the water-based acrylic varnish is calculated in parts by weight and includes: 70-90 parts of water-based oligomeric acrylic emulsion, 8-16 parts of acrylic acid, 1-2 parts of dispersant, 0.5-1 parts of defoamer, 0.04-0.1 parts of photosensitizer, 0.6-1.2 parts of leveling agent, 0.1-0.3 parts of neutralizer and 25-35 parts of deionized water; The preparation method of the water-based oligomeric acrylic emulsion comprises: S1, weigh 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol, mix them, stir them until they are uniform, add a catalyst, heat them to reflux, keep them warm and stir for 4-6 hours, and after the reaction is completed, remove impurities by rotary evaporation to obtain olefin benzimidazole; S2, mixing olefin benzimidazole, the first emulsifier and deionized water, then adding acrylic acid monomer, and stirring and mixing for 20-40 minutes to obtain a pre-reaction solution; S3. Under the protection of nitrogen, mix the initiator, the second emulsifier and deionized water, and heat to 65-75°C. After stirring evenly, add the pre-reaction liquid dropwise, and control the dropping time to 1-2h. After the dropping is completed, heat to 75-85°C, stir at this temperature for 1-2h, and cool to room temperature to obtain an aqueous oligomeric acrylic emulsion.

2. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In step 2, the ink is embossed and then subjected to UV curing treatment, with a UV wavelength of 365 nm and a radiation dose of 100-200 mW / cm 2 , the curing time is 1-5min.

3. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In step 3, the curing is carried out by UV curing, the UV wavelength is 365nm, and the radiation amount is 100-200mW / cm 2 , the curing time is 1-5min.

4. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In S1, the mass ratio of 2-aminobenzimidazole, 3-methyl-2-butenal and isopropanol is 1.4-1.8:0.8-1.2:10-20; the catalyst is triethylamine, and the added amount is 3%-5% of the mass of 3-methyl-2-butenal.

5. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In S2, the mass ratio of olefin benzimidazole, acrylic monomer, first emulsifier and deionized water is 0.3-0.7:1.7-3.9:0.03-0.08:20-30.

6. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In S2, the acrylic acid monomers include acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, and cyclohexyl methacrylate, and the mass ratio of acrylic acid, methacrylic acid, butyl acrylate, methyl methacrylate, isooctyl methacrylate, and cyclohexyl methacrylate is 0.3-0.5:0.2-0.6:0.3-0.7:0.1-0.5:0.4-0.8:0.4-0.

8.

7. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: In S3, the initiator is one of sodium persulfate, potassium persulfate and ammonium persulfate; the mass ratio of the initiator, the second emulsifier, the pre-reaction liquid and the deionized water is 0.05-0.1:4-8:50-100:50-100.

8. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: The first emulsifier in S2 and the second emulsifier in S3 are the same, and are one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate, and sodium hexadecylbenzene sulfonate.

9. The method for preparing a composite coating decorative embossed glass with high hardness and high adhesion according to claim 1, characterized in that: The dispersant is Digo 760W, the defoamer is Digo 902W, the photosensitizer is photosensitizer 1173, the leveling agent is BYK-333, and the neutralizer is ethanolamine.

Citation Information

Patent Citations

  • Production process for microstructural texture colour crystal glass

    CN105563959A

  • Water-based ink capable of being quickly cured

    CN111378316A